On Territorial Competition between Rhinoceros Sondaicus and Bos Javanicus at Ujung Kulon National Park - Harjanto, Eric (Communication in Biomathematical Sciences, 2017)
In this paper, we consider the interaction between Rhinoceros Sondaicus, known as Javan Rhino, and Bos Javanicus, known as Javan Bull, at Ujung Kulon National Park. For years, the population of Javan Rhinos never exceeds their estimated carrying capacity, despite their vast habitat and there is no natural predator in the area. Both species naturally consume different food resources, hence there is no direct competition on food resource between the two species. This stagnant growth of Javan Rhino is suspected due to the territorial competition between the two species, in which the rapid growth of Javan Bull may reduce the territory of Javan Rhino and consequently reduce the carrying capacity of Javan Rhino. We construct a mathematical model ofterritorial competition between two species and show that domination of one species can lower the carrying capacity of the second species.